RIVALITAS “PALSU” DALAM PEMILIHAN KEPALA DESA (Studi Kasus Suami Melawan Istri dalam Pemilihan Kepala Desa Karangrau Sokaraja Banyumas Tahun 2021) - Syaiana, Fitri Nur; Sardini, Nur Hidayat -; -, Supratiwi - (Journal of Politic and Government Studies, 2024)
The implementation of Pilkades is guided by Peraturan Menteri Dalam Negeri Nomor 65 Tahun 2017 concerning the Election of Village Heads. The regulation explicitly states that the Pilkades should be attended by at least two candidates and at most three candidates. In turn, the limitation on the number of candidates for village heads has given rise to an interesting phenomenon: there are pairs of candidates who are husband and wife in the 2021 Pilkades of Banyumas Regency in Karangrau Village. This research was conducted to analyze the rivalry that actually occurred in the phenomenon of married couples' Pilkades in Karangrau Village Sokaraja Banyumas in 2021. This was done through analyzing the contestation and competition in it using dramaturgy theory through facts in the front stage and back stage. This research uses a qualitative method of case study type with in-depth interviews with informants as an instrument in collecting data. The results of this study show that the wife's candidacy was carried out as a tactic to avoid a single candidate, thus presenting a pseudo-contestation and fake rivalry designed only to fulfill obligations. There are differences between the front stage and the back stage. On the front stage, normatively all stages in the Pilkades run naturally and normally, but on the back stage there is no competition that occurs but there is cooperation to win the incumbent village head candidate (husband). Then there was no community participation to run as a village head candidate. To improve this reality, it is best to evaluate the regulations on Pilkades and emphasize the requirements for candidacy so that close relatives such as husband, wife, brother, sister, or child do not participate. Empowerment of human resources at the village level oriented towards leadership regeneration is also needed to encourage community interest in running for village head